Accounting Software Application Education for Dayah Darul Hikmah Management - Simbolon, Deliyanti; Wahyuni, Putri; Pane, Yonson; Syahrizal, Teuku Muhammad; Amri, Khoirul (Eastasouth Institute, 2025)
This community service activity aims to improve the understanding and management skills of Dayah Darul Hikmah in preparing financial reports using accounting software applications to minimize the occurrence of errors and more effective and transparent financial management. So far, the financial recording process at Dayah Darul Hikmah is still done manually, which is prone to errors and less efficient. Through intensive training and mentoring provided, the implementation team introduces and trains the use of computer-based accounting software that is in accordance with the needs of the institution. The method of implementing activities includes initial preparation and surveys, Implementation Program Education and Training, Mentoring and Evaluation of participants' understanding results. The results of the activity showed a significant increase in participants' understanding of the use of accounting software in preparing financial reports. This activity is expected to increase accountability and transparency with the use of accounting software for the management of the Darul Hikmah Islamic Boarding School towards better and more professional Islamic boarding school financial governance.